Low threshold T‐type calcium channels as targets for novel epilepsy treatments. (May 2014) - Powell, Kim L.; Cain, Stuart M.; Snutch, Terrance P.; O'Brien, Terence J.
<x xml:space="preserve">Abstract</x> Low voltage‐activated T‐type calcium channels were originally cloned in the 1990s and much research has since focused on identifying the physiological roles of these channels in health and disease states. T‐type calcium channels are expressed widely throughout the brain and peripheral tissues, and thus have been proposed as therapeutic targets for a variety of diseases such as epilepsy, insomnia, pain, cancer and hypertension. This review discusses the literature concerning the role of T‐type calcium channels in physiological and pathological processes related to epilepsy. T‐type calcium channels have been implicated in pathology of both the genetic and acquired epilepsies and several anti‐epileptic drugs (AEDs) in clinical use are known to suppress seizures via inhibition of T‐type calcium channels. Despite the fact that more than 15 new AEDs have become clinically available over the past 20 years at least 30% of epilepsy patients still fail to achieve seizure control, and many patients experience unwanted side effects. Furthermore there are no treatments that prevent the development of epilepsy or mitigate the epileptic state once established. Therefore there is an urgent need for the development of new AEDs that are effective in patients with drug resistant epilepsy, are anti‐epileptogenic and are better tolerated. We also review the mechanisms of action of the current AEDs with known effects on T‐type calcium channels and discuss novel compounds that are being investigated as new treatments for epilepsy.